GREEN INNOVATION IN BATAM CONSTRUCTION COMPANIES: THE ROLE OF ORGANIZATIONAL CLIMATE AND CORPORATE GOVERNANCE - Selvia Suhaeda; Yandra Rivaldo; Dewi Permata Sari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
The construction industry is one of the most environmentally intensive sectors, making green innovation an essential strategy for improving environmental sustainability and organizational competitiveness. This study aims to analyze the effects of organizational climate, corporate governance, and employee intellectual capability on green innovation, as well as to examine the moderating role of green transformational leadership in construction companies in Batam City, Indonesia. The study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Data were collected from 82 employees working in construction firms through purposive sampling and measured using a Likert-scale questionnaire. The findings indicate that organizational climate, corporate governance, and employee intellectual capability each have a positive and significant effect on green innovation, with employee intellectual capability emerging as the strongest predictor. Green transformational leadership also has a direct positive effect on green innovation. However, it does not significantly moderate the relationship between organizational climate, corporate governance, employee intellectual capability, and green innovation. These results suggest that internal organizational factors and employee capacity play a central role in encouraging green innovation. The study concludes that strengthening intellectual capability, fostering a supportive organizational climate, and implementing sound corporate governance are key strategies for promoting green innovation in construction companies.